An electret-based aeroelastic flutter energy harvester. (3rd February 2015) - Perez, M; Boisseau, S; Gasnier, P; Willemin, J; Reboud, J L
Abstract: This paper presents a new airflow energy harvester exploiting fluttering effects coupled to an electret-based conversion to turn the flow-induced movements of a membrane into electricity. The proposed device is made of a polymer membrane placed between two parallel flat electrodes coated with 25 μ m thick Teflon PTFE electret layers; a bluff body is placed at the inlet of the device to induce vortex shedding. When the wind or airstream of any kind flows through the harvester, the membrane enters in oscillation due to fluttering and successively comes into contact with the two Teflon-coated fixed electrodes. This periodic motion is directly converted into electricity thanks to the electret-based conversion process. Various geometries have been tested and have highlighted a 2.7 cm 3 device, with an output power of 481 μ W (178 μ W cm −3 ) at 15 m s −1 and 2.1 mW (782 μ W cm −3 ) at 30 m s −1 with an electret charged at −650 V. The power coefficient C p of the device reaches 0.54% at 15 m s −1 which is low, but compares favorably with the other small-scale airflow energy harvesters.